Anthropometric indices of the newborns related with some lifestyle parameters of women during pregnancy in Tirgu Mures region - a pilot study - Iacob, Oana Maria; Bacarea, Anca; Ruta, Florina Daniela; Bacarea, Vladimir Constantin; Gliga, Florina Ioana; Buicu, Florin; Tarcea, Monica; Avram, Calin; Costea, George Claudiu; Sin, Anca Ileana (Progress in Nutrition, 2018)
Objective: We aim to study possible associations between lifestyle, socio-economic aspects, educa-tion and dietary habits during pregnancy and both the incidence of premature deliveries and anthropometric characteristics of newborns in different ethnic Romanian populations. Methods: This is a cross-sectional, questionnaire-based retrospective study applied on puerperal women from Tirgu-Mures, Romania. Anova and Kruskall Wallis were the statistical tests used. Results: Deficient intake of dairy products was found in the Romani women (69.50%), of red meat in Romanians (23.20%), of white meat in Hungarians (83.40) and Romanians (77.50%), of fish and eggs in Romani (91.30%) and Hungarian women (89.6%), of vegetables in Hungarian (93.80%) and the Romani women (91.3%) and of whole grain cereals in Romanian (93.40%) and Hungarian (95.50%) women. The water intake below the daily needs was found in 49.30% of Roma-nian women, 47.60% of Hungarian women and 100% of Romani women. An increased consumption of to-bacco (p